Direct plasmadynamic synthesis and preparation of superdispersed Ti–Si–N compositions; Nanotechnologies in Russia; Vol. 12, iss. 5-6 - Sivkov A. A. Aleksandr Anatolyevich; Gerasimov D. Yu. Dmitry Yurievich; Evdokimov A. A. Andrey Anatolievich; Saigash A. S. Anastasiya Sergeevna (2017, 2017)
Title screen